Nocturnal GERD – a risk factor for rhinitis/rhinosinusitis: the RHINE study. Issue 6 (6th April 2015) - Schiöler, L.; Ruth, M.; Jõgi, R.; Gislason, T.; Storaas, T.; Janson, C.; Forsberg, B.; Sigsgaard, T.; Torén, K.; Hellgren, J.
Abstract: Background: It has been suggested that gastroesophageal reflux disease (GERD) is a risk factor for developing rhinitis/rhinosinusitis, but data are lacking. This is a prospective 10‐year follow‐up study of a large multicenter cohort from Northern Europe, evaluating the relationship between nocturnal GERD and noninfectious rhinitis (NIR). Methods: The study comprised 5417 subjects born between 1945 and 1973, who answered a questionnaire in 1999–2001 and again in 2010–2012. Noninfectious rhinitis was defined as having nasal obstruction, secretion, and/or sneezing without having the common cold. Odds ratios for developing NIR in relation to age, gender, BMI, smoking, asthma, and nocturnal GERD were calculated. Results: During the 10‐year observation period, 1034 subjects (19.1%) developed NIR. Subjects reporting nocturnal gastroesophageal reflux in both 1999 and 2010 had more NIR in 2010 (2.8% vs 1.2%, P < 0.001). There was a significant dose–response relationship between the number of reflux episodes/week in 1999 and the risk of having NIR in 2010, P = 0.02. In the multiple regression adjusted for age, gender, BMI, tobacco smoke, and asthma, those with nocturnal GERD in 1999 (≥3 episodes of nocturnal gastroesophageal reflux symptoms per week) had an OR of 1.6 (95% CI 1.0–2.5, P = 0.03) to develop NIR in 2010. Smoking was associated both with an increased risk of developing NIR (30.7% vs 24.0%, P < 0.001) and with the development of nocturnal GERD. Conclusion: This large, population‐based, 10‐year study indicates that nocturnal GERD was a risk factor for noninfectious rhinitis/rhinosinusitis. GERD should therefore be considered in patients with rhinitis of known and unknown origin.